Moving bed biofilm reactor with immobilized low-density polyethylene–polypropylene​ for Congo red dye removal - Sonwani R.K.; Swain G.; Jaiswal R.P.; Singh R.S.; Rai B.N. (My University, 2025)
The wastewater containing the azo dye is a global environmental challenge among researchers. In this study, an effort has been made to use a modified carrier (i.e., low-density polyethylene–polypropylene(LDPE-PP)) to remove the Congo red (CR) dye from synthetic wastewater in a moving bed biofilm reactor (MBBR). The effect of CR dye concentration (25 to 300 mg/L), hydraulic retention time (HRT) (12 to 96 h) under the batch mode, and inlet loading rate (ILR) (40 to 320 mg/L day) under the continuous mode were examined. The highest removal efficiency (RE) and elimination capacity (EC) of CR dye were obtained as 99.2% and 214.4 mg/L day, respectively. Three models, namely first-order, Grau second-order, and modified Stover–Kincannon (S–K) were applied to study the kinetic aspects. The highest correlation coefficient (R2) was obtained for the modified S–K model, and the saturation constant (KB) and maximum substrate removal rate (Umax) were estimated as 0.67 g/L day and 0.71 g/L day, respectively. The proposed kinetic equations can predict the effluent concentration and estimate the bioreactor volume to scale up the process. © 2021 Elsevier B.V.